Las cárceles que son pena de muerte. El caso ecuatoriano - ARROBO Fernández, María Lorena (Eguzkilore, 2022)
The Constitution of the Republic of Ecuador recognizes and guarantees the right to inviolability of life, emphasizing that there will be no death penalty. In addition, there is a prohibition of torture, forced disappearance and cruel, inhuman or degrading treatment and punishment. However, the prison crisis that the country is going through has led social rehabilitation centers to become the ideal place for torture, cruel, inhuman and degrading treatment and even death, since the mere act of entering prison it has constituted and constitutes for many people deprived of liberty, the death penalty. In this context, the Ecuadorian State becomes one more that constitutionally denies the death penalty, but in reality, many end up dying in prison. In this paper I intend to address the prison crisis and the serious problems that overcrowding entails, make a chronology of the atrocious events that occurred within the social rehabilitation centers, emphasizing the massacres recorded in the year 2021, where it is evident that the The cruelty of prison currently involves countless suffering, humiliation, cruel, inhuman and degrading treatment, torture and even death, to finally write down some reflections by way of conclusion.